Implementing Audiovisual Media and Group Discussions as an Educational Strategy for Anemia Prevention Among Adolescents in the Work Area of Public Health Center X, Magetan - Ineke Permatasari (Journal Ligundi of Community Service, 2025)
Background. Anemia among adolescents remains a significant public health issue in Indonesia. Data from the 2021 Indonesian Nutritional Status Survey (SSGI) indicates that the prevalence of anemia among adolescents aged 15-24 years is 26.5%, with a higher proportion in adolescent girls (32.0%) compared to adolescent boys (20.3%). This condition has serious implications for reduced productivity and learning capacity. Conventional education is considered less effective for the adolescent group, necessitating innovative approaches tailored to the characteristics of Generation Z. Purpose. To implement and evaluate the effectiveness of combining audiovisual media and group discussions in improving adolescents' knowledge and attitudes toward anemia prevention in the work area of Public Health Center X, Magetan. Method. The activity was conducted with 25 adolescents, consisting of 7 anemic and 18 non-anemic adolescents. The intervention involved showing infographic animation videos on anemia prevention followed by guided group discussions. Data were collected using knowledge questionnaires (pre-test and post-test) and observation sheets to assess changes in participants' attitudes. Data analysis utilized the paired t-test with a significance level of p < 0.05. Results. There was a significant increase in knowledge, with the average post-test score (85.2 ± 7.1) being higher than the pre-test (58.5 ± 10.4) at p < 0.001. Approximately 88% of participants demonstrated positive attitudes and a commitment to implementing balanced nutritional eating patterns and consuming iron-folic acid (IFA) tablets regularly. Observation results showed active participant engagement in group discussions and enthusiasm in following the audiovisual materials. Conclusion. The combination of audiovisual media and group discussions is proven effective in increasing knowledge and fostering positive attitudes toward anemia prevention among adolescents. This method can be adopted as an innovative health education model for adolescents and is recommended for implementation in various primary healthcare settings.